The social representations on climate change of the students of pedagogy in Mexico: An approach from the perspective of gender - Raúl Calixto Flores (Pontificia Universidad Católica del Perú, 2019)
This article describes the results of a research carried out with students of pedagogy of the National Autonomous University of Mexico and of the National Pedagogical University, of Mexico in order to identify the social representations they have about climate change; we used the interview, the survey with a semi-structured questionnaire and a questionnaire with Lickert-type scale and an associative letter. The obtained results the existence of social representations of the climate change; with similar characteristics between the students (female and male) and more favorable attitudes in the students (female). In general, the components of social representations dimensions are similar by gender and by university. In the representations, information on the effects of climate change and the recognition of the importance of environmental education predominate.